The Application of Dividend Yield Based Investment Strategy in Indonesian Stock Exchange - Ekaputra, Adriansyah; Sukarno, Subiakto (The Indonesian Journal of Business Administration, 2012)
Stock market development in Indonesia is growing rapidly, coupled with the increase of Indonesia’s investment rating by investment research and rating companies such as Moody’s and S&P, it makes Indonesian stock market look sexy in the eyes of investors from various countries. The investment strategy that simple and applicable is often sought by investors to maximize the investors’ portfolio. One investment strategy is evolving but still not widely used in Indonesia is an investment strategy based on dividend yield. Dividend yield based investment strategy such as the Dogs of the Dow is quite popular in the United States, but the use of this investment strategy in Indonesia is still quite uncommon. Therefore, the expected investment strategy in Indonesia may provide a favorable outcome. The main issue of writing this final project is whether the application of dividend yield based investment strategy on the Indonesia stock exchange, especially in LQ45 stock index so that it can produce such good results as on the Dow Jones stock index. The research to analyze the application of dividend yield based investment strategy used historical data of LQ45 stocks from period 2006 to 2011. Closing prices of the end of the year and the annual dividend of the companies are the components to calculate dividend yield. The portfolio is formed from the 10 highest dividend yield stocks. The research show that dividend yield based investment strategy can give high performance and also simple to apply. With an investment strategy that provides a profitable portfolio for investors, investment companies may also attract investors to invest in their products. Individual investor could also develop their portfolio using the investment strategy to maximize their profit themselves. Keywords: Indonesian stock exchange, dividend yield, investment strategy.